Exploring the Lived Experiences of Female School Principals in Their Relationships with Students - Jabalhang , Shahin; Maleki Avarsin, Sadegh; Yari Haj Ataloo , Jahangir (Assessment and Practice in Educational Sciences, 2026)
The objective of this study was to explore and interpret the lived experiences of married female principals in girls’ upper secondary schools regarding their interactions and relationships with students. This study employed a qualitative research design grounded in descriptive phenomenology to capture the essence of principals’ lived experiences. The participants consisted of twelve married female principals working in public girls’ upper secondary schools across five educational districts of Tabriz. Participants were selected through purposive and theoretical sampling based on defined inclusion criteria, and data collection continued until theoretical saturation was achieved. Data were gathered through in-depth semi-structured interviews designed to elicit rich narratives about principals’ daily experiences with students. Interviews were audio-recorded, transcribed verbatim, and analyzed concurrently with data collection. Colaizzi’s seven-step phenomenological method was used to systematically analyze the data, and strategies such as prolonged engagement, member checking, and careful coding review were applied to ensure credibility and dependability. Data analysis resulted in the identification of a central theme labeled students’ issues, encompassing several interrelated sub-themes. These included the necessity of human relationships and addressing students’ emotional deprivation, low academic motivation, the need for self-care programs, academic decline associated with marriage and migration, non-compliance with health care practices, lack of interest in technical and vocational tracks, the impact of parental divorce, and spousal opposition to continued education. Collectively, these findings indicate that principals experience student-related challenges as emotionally intensive, multifaceted, and deeply embedded in students’ social and familial contexts. The findings demonstrate that interactions with students constitute a core dimension of female principals’ leadership experiences, characterized by emotional labor, ethical responsibility, and relational engagement, underscoring the need for leadership support structures that address both academic and psychosocial aspects of schooling.